1979
DOI: 10.3758/bf03209696
|View full text |Cite
|
Sign up to set email alerts
|

The effects of qualitative and quantitative variation in the US on individual components of Pavlovian appetitive conditioned behavior in rats

Abstract: The form of rats' Pavlovian conditioned responses to visual and auditory conditioned stimuli (eSs) paired with a variety of unconditioned stimuli (USs) was examined in three experiments using direct behavioral observation techniques. In Experiment 1, the form of conditioned behavior occurring most frequently during later portions of the es-us interval depended only on which of several appetitive USs was used, but the form of behavior occurring most frequently during early portions of the es-us interval depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
2
2

Year Published

1981
1981
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 10 publications
8
52
2
2
Order By: Relevance
“…First, the ability of the CSs to evoke magazine behaviors is in line with many other reports of the effects of pairing discrete CSs with food USs in rats (Holland, 1977;1979a, 1979bKaye & Pearce, 1984). Such behaviors have fre-quently been used to index successful conditioning.…”
Section: Resultssupporting
confidence: 59%
“…First, the ability of the CSs to evoke magazine behaviors is in line with many other reports of the effects of pairing discrete CSs with food USs in rats (Holland, 1977;1979a, 1979bKaye & Pearce, 1984). Such behaviors have fre-quently been used to index successful conditioning.…”
Section: Resultssupporting
confidence: 59%
“…The present findings are also consistent with the view that Pavlovian conditioned behavior consists of the convergent action of multiple, independently formed associations (Holland, 1977(Holland, , 1979(Holland, , 1980. To borrow a phrase from Holland and Straub's (1979) work on food conditioning, the results of Experiments 2 and 3 indicate that conditioned appetitive and consummatory sexual behaviors "are to some extent independent and cannot be viewed as forming a unitary conditioned response" to sexually conditioned stimuli (p. 78).…”
Section: Discussionsupporting
confidence: 78%
“…Holland (1977Holland ( ,1979Holland ( ,1980 suggested that CS-US relations result in "two quite independent types of conditioned behavior to the CS-a response appropriate to the US, perhaps as a consequence ofa stimulus substitution process (e.g., Mackintosh, 1974), and enhancement of the orienting response originally elicited by the CS" (1979, p. 431). Holland based this proposal in part on the observation that certain "early" components of the CR antecedent to food delivery were less influenced by the nature (food vs. sucrose) and the magnitude ofthe US than "later" components.…”
Section: Discussionmentioning
confidence: 99%
“…Our measure did not permit any statement about what these other behaviors might be; informally, however, it seemed to us as though the light elicited more rearing (cf. Holland, 1979).2 This finding, that the light and noise elicited similar levels of barpress suppression whereas the noise controlled more freezing, is directly relevant to the discussion of modality differences by Sigmundi and Bolles (1983). Finding that their noise elicited more freezing, Sigmundi and Bolles wondered whether the noise was better conditioned or whether noise and light controlled defensive behaviors that differed in form.…”
Section: Discussionmentioning
confidence: 97%